Absence of spinocerebellar ataxia type 3/Machado-Joseph disease within ataxic patients in the Czech population - Bauer, P O; Zumrova, A; Matoska, V; Marikova, T; Krilova, S; Boday, A; Singh, B; Goetz, P (European journal of neurology, 2005)
Although spinocerebellar ataxia type 3 (SCA3)/Machado-Joseph disease is the most common type of SCA worldwide, we did not identify any cases of the disease amongst SCA patients in the Czech population. It has been proposed that the prevalence of large normal alleles correlates with the frequency of various types of SCA. We have therefore attempted to resolve the absence of SCA3 in our population by investigating, within 204 normal chromosomes, the frequency and nature of CAG repeats as well as two intragenic polymorphisms. We found that large normal alleles with more than 33 CAG repeats were observed at a frequency of only 0.49%. Whereas most of the expanded alleles worldwide have the CA haplotype, this was the least common (5.4%) variant observed in our study, although it was associated with a larger mean CAG repeat length (26.9). We postulate that the absence of SCA3 in the Czech population might be explained by the lack of large normal alleles and consequently a relatively small reservoir for aberrant CAG expansions at the SCA3 locus.
Keywords: represorové proteiny; Trinucleotide Repeats; alely; Humans; Mutation; Gene Frequency; Ataxin-3; Repressor Proteins; Czech Republic; Nuclear Proteins; jaderné proteiny; Polymorphism, Genetic; Česká republika; polymorfismus genetický; spinocerebelární ataxie; mutační analýza DNA; frekvence genu; Nerve Tissue Proteins; DNA Mutational Analysis; trinukleotidové repetice; Machado-Joseph Disease; lidé; ataxin-3; mutace; Spinocerebellar Ataxias; proteiny nervové tkáně; Machado-Josephova nemoc; Alleles